Just transitions: A review of how to decarbonise energy systems while addressing poverty and inequality reduction - Daniele Malerba (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
Germany promotes 'just transition' as a guiding principle for the global transition to a socially and environmentally sustainable economy that incorporates the necessary climate, environmental and energy policy measures. This includes the urgent transformation of economies to become emission neutral while ensuring a process whereby poverty and inequality are reduced, and no one is left behind.The German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE), the World Bank and the German Federal Ministry for Economic Cooperation and Development (BMZ) worked together to explore ways to implement the concept of just transition in German development cooperation. The two papers that have resulted from this process outline approaches to a 'just transition for all' and highlight its potential to reduce poverty and inequality (SDG 1 and SDG 10). [...]
Keywords: 330